La construcción de políticas y estrategias de comunicación para la conservación de la biodiversidad en el Ecuador - Bueno Cerda, María Belén (2014)
The main objective of this thesis is to develop policies and communication strategies for the care of the environment, to prevent further increasing environmental problems. This campaign was created "Vivamos en Armonía", which has used the technology, and especially the media to disseminate information on the rights that nature, so we can generate dialogue and citizen participation in environmental issues. This initiative builds on the concepts of communication, development, ecology, sustainable development, environmental communication, strategy and policy; when talking communication we refer to social interaction, is a social resource that offers a wide variety of natural features, which make it capable to support any process of social change.